A PROJECT JOURNAL THE EXTENDED SELF IN POSSESSING VANSSHOES - Paramita, Afrianeke FirstinandaPutri (LANTERN (Journal on English Language, Culture and Literature), 2017)
People usually will choose one popular culture as their lifestyle. Music, movie, fashion, food, drink, and sport are several artifacts or products of popular culture.